Fiscal Policy and Macroeconomic Shocks in Nigeria: A Structural Vector Auto - Regression SVAR Approach - Patrick, Ologbenla; Adeleke, Omolade (Journal of Economics and Behavioral Studies, 2018)
The paper investigates fiscal policy and macroeconomic shocks in Nigeria. It was motivated by the non - existence of consensus on the nature and levels of interactions between fiscal policy variables and macroeconomic variables. The study utilizes quarterly data from 1980 Q1 to 2015 Q4 which are analyzed using Structural Vector Auto - Regression (SVAR) to examine the responses of fiscal policy to some macroeconomic shocks and vice versa. The results indicate that exchange rate is the major macroeconomic medium through which external shocks influence fiscal policy variables in Nigeria. The level of interaction between fiscal policy variables and exchange rate, among other macroeconomic variables in the model, appears to be the most significant. Also, among all other macroeconomic variables the contributions of the exchange rate to the behavior of Nigeria’s economic growth is the highest. All these are pointers to the significant role played by exchange rate in transmission of macroeconomic and external shocks to fiscal policy behavior with the resultant effect on the domestic economy.